Corporate social responsibility : a public's perception. - Gui, Siew Kheng. (2008)
Corporate social responsibility (CSR)is a recent business concept in Singapore. The growing trend to be more socially involved is the recognition of the benefits from CSR. This project seeks to uncover the public’s perception of CSR and to obtain an insight into its level of awareness in Singapore.